Evaluation of byproducts of Solanum tuberosum and Daucus carota by FES as an alternative in animal feed (2021)
The growing demand for foods such as corn or soybeans has favored the implementation of biotechnologies through the use of agro-industrial waste in order to obtain alternative diets with high biological value. For this reason, the objective of this research was to develop a diet based on harvest by-products of potato Solanum tuberosum and carrot Daucus carota treated by Solid State Fermentation (FES). Postharvest quality analysis was carried out, subsequently, they were mixed in a proportion of 15% together with palm kernel (20%), wheat ceme (20%), soybean cake (10%), corn (10%), coffee husk (5%), molasses (4%) and additives such as vitamin premix (0.5%) and bacterial inoculant (0.5%). The prepared food was then subjected to FES and evaluated by compositional and microbiological analysis. Descriptive statistical analysis of the evaluated variables was performed and DM values ​​of 66.7%, humidity 33.3%, crude protein 19.4%, ash 5.21%, ether extract 6.35% and crude fiber 16,9% were obtained. The microbiological analysis determined that the aerobic mesophil count was exponentially higher at 48 hours compared to 72 hours (110.67 ± 23.44), no growth of molds and yeasts was observed at 48 hours and at 72 hours they were reported (14.67 CFU / g ± 5.03). It is concluded that by using FES the biological value of potatoes and carrots can be increased in a mixture with other raw materials to obtain diets intended for animal feed.